THE EFFICACY OF SILDENAFIL THERAPY IN PATIENTS WITH PULMONARY HYPERTENSION OF DIFFERENT ETIOLOGY: INFLUENCE ON THE CLINICAL, FUNCTIONAL, HEMODYNAMIC STATUS, STRUCTURE AND FUNCTION OF THE RIGHT AND LEFT HEART, RIGHT VENTRICULAR-ARTERIAL COUPLING - T. V. Martynyuk; Z. H. Dadacheva; V. M. Paramonov; M. A. Saidova; S. N. Nakonechnikov; I. Ye. Chazova (Евразийский Кардиологический Журнал)
Aim: to study the efficacy of sildenafil therapy in pulmonary hypertension of different etiology, its influence on the clinical, functional, hemodynamic status, structure and function of the right and left heart, right ventricular-arterial coupling (RVAC) in pts with idiopathic pulmonary hypertension (IPAH) and chronic thromboembolic pulmonary hypertension (CTEPH).Materials and methods: in the study we included 29 IPAH pts aged 42.8±10.6 yrs, 28 CTEPH pts aged 43.4±10.4 yrs II-IV functional class (FC) (WHO), receiving stable standard therapy (anticoagulants, diuretics, glycosides) and calcium channel blockers for at least 3 months. Sildenafil was started at the dose of 10 mg TID to assess the tolerability for further titration after 1 wk to 20 mg 3 times a day. The treatment duration was 16 wks. At baseline and at wk 16 FC (WHO), 6-minute walking test (6-MWT), transthoracic echocardiography (Echo) and right heart catheterization (RHC) were performed.Results: both groups were comparable in baseline functional parameters: FC, the distance in 6-MWT, Borg index. The analysis of baseline structural and functional cardiac parameters by Echo in IPAH and CTEPH pts revealed pronounced cardiac remodeling as compared to the control group. All pts had criteria precapillary PH by RHC with comparable systolic pulmonary artery pressure (SPAP), mean pulmonary artery pressure (PAPm), cardiac output (CO) and index (CI), pulmonary vascular resistance (PVR) except for diastolic PAP (DPAP), which was higher in IPAH group (38.3±13.7 mm Hg vs 31.5±8.9 mm Hg in CTEPH group (p<0.05). Sildenafil therapy resulted in the marked improvement of functional and hemodynamic status, cardiac remodeling parameters in both groups. To wk 16 IPAH pts achieved the 114m increase in 6-MWT as compared with 108m in CTEPH group. IPAH pts demonstrated the significant decrease in SPAP, PAPm, reduce of right ventricular (RV) size and improvement of contractile function - FAC and TAPSE, increase of RVAC by reducing LV stiffness. Eccentricity index of LV improved significantly only in CTEPH pts. Positive dynamic in RHC data (significant decrease of SPAP, PAPm, DPAP, PVR, increase of CO,CI, stroke volume). CTEPH pts showed a greater reduction in PVR, SPAP and significant SvO2 improvement.Conclusion: 1. In pts with IPAH and CTEPH of comparable baseline clinical, functional and hemodynamic status we found no significant differences in the severity of cardiac remodeling, RV and LV systolic and diastolic function. Regardless of etiology RVAC was reduced due to the significant increase of LV stiffnessEs. 2. 16-wk sildenafil therapy in pts with IPAH and CTEPH resulted in the positive dynamic of 6-MWT distance, dyspnea index, Echo data including LV stiffness. 3. In CTEPH group as compared with IPAH pts we found the more marked reduction in PVR, PASP and significant improvement SvO2 by RHC. The significant decrease in Es was observed only in CTEPH pts.